Learning with Letter Cards in Literacy Introduction for Children Aged 4-5 Years at Taman Firdaus Islamic Kindergarten Karanganyar - Kusminati, Lis; Slamet, Sri (Universitas Muhammadiyah Surakarta, 2023)
This study investigates the efficacy of letter cards in fostering early literacy skills among children aged 4-5 years at TK Islam Taman Firdaus Karanganyar. Early literacy constitutes a pivotal aspect of a child's developmental journey, and employing suitable pedagogical approaches can significantly enhance reading and writing proficiencies during formative years. Employing a qualitative methodology coupled with a case study research design, this study engages kindergarten educators in Karanganyar who have integrated letter cards into their literacy curriculum. Data collection methodologies encompass classroom observations, teacher interviews, and document scrutiny. Findings underscore the effectiveness of utilising letter cards in initiating early literacy activities at TK Islam Taman Firdaus Karanganyar. Letter cards prove instrumental in facilitating letter recognition, word formation, and eventual fluency in reading. Furthermore, this approach fosters heightened interest among children in reading and writing activities. Noteworthy is the pivotal role of educators in orchestrating learning experiences with letter cards, ensuring alignment with the developmental requisites of 4-5-year-olds.